Exploring the role of multidrug exporters and extracellular vesicles in medulloblastoma chemoresistance - Wade, Philippa (2024)
Introduction: Medulloblastoma is the most common malignant paediatric brain tumour; patients harbouring relapsed and metastatic tumours exhibit a dismal 5-year survival prognosis, where less than 10% of patients respond to current treatments. Whilst there have been considerable steps forward in our understanding of the molecular biology underpinning medulloblastoma, our understanding of relapsed medulloblastoma remains incredibly limited. The high frequency of recurrence observed in patients not only highlights an urgent and unmet need to identify new therapeutic targets, but it also indicates the presence of intrinsic drug resistance mechanisms. Multidrug exporters and extracellular vesicles have been implicated in chemoresistance in several cancers, the former exerting effects through drug efflux and the latter through the transfer of biologically active cargo. Whilst multidrug exporter ABCB1 has previously been associated with high-risk medulloblastoma and therapy resistance, the roles of additional multidrug exporters and extracellular vesicles in medulloblastoma chemoresistance are yet to be explored. This study, therefore, set out to examine both the role of extracellular vesicles and the contribution of multidrug transporters ABCB1, ABCC1 and ABCG2 to medulloblastoma chemoresistance.